Insiders, Outsiders, Skills, and Preferences for Social Protection: Evidence From a Survey Experiment in Argentina - Menéndez González, Irene (Comparative political studies, 2021)
Standard theories in comparative political economy predict that labor market insiders oppose redistribution to poorer, often informal, labor market outsiders. In contrast, I argue that not all insiders oppose redistribution to outsiders. Extending recent work emphasizing the importance of economic insecurity for insiders, I argue that exposure to risk leads to greater polarization regarding preferences for non-contributory social policy between low- and high-skilled insiders. I test implications of this logic using a survey experiment from a nationally representative sample in Argentina and complement this with analysis of observational data for 16 Latin American countries. I find strong evidence of polarization regarding preferences over social protection among low- and high-skilled insiders. The experiment reveals that low (high)-skilled insiders primed about the risk of becoming outsiders become more supportive of transfers to outsiders (insiders). The article provides new micro-foundations for insider–outsider coalitions in support of social policy expansion in middle-income countries.